2017
DOI: 10.1101/221036
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multi-scale periodicities in the functional brain networks of patients with epilepsy and their effect on seizure detection

Abstract: Highlights-We have examined the long-term characteristics of EEG functional brain networks and their correlations to seizure onset -We show periodicities over multiple time scales in network summative properties (degree, efficiency, clustering coefficient) -We also show that, in addition to average network properties, the same periodicities exist in network topology using a novel measure (graph edit distance), suggesting that specific connectivity patterns recur over time -These periodic patterns were preserve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 47 publications
2
8
0
Order By: Relevance
“…For all patients, the instantaneous phases at the onset of the seizure were collected and the obtained phase distribution were subsequently investigated using CircStat which is a Matlab (Math works, Natick MA) toolbox related to circular statistics (Berens, 2009 ). For more details, the reader is referred to Mitsis et al ( 2018 ). To investigate whether phase values at seizure onset times were distributed uniformly around the circle from 0 to 2π, we applied the Rayleigh test with the null hypothesis ( H 0 ) being that the population is distributed uniformly around the circle.…”
Section: Eeg Recordings and Preprocessingmentioning
confidence: 99%
See 1 more Smart Citation
“…For all patients, the instantaneous phases at the onset of the seizure were collected and the obtained phase distribution were subsequently investigated using CircStat which is a Matlab (Math works, Natick MA) toolbox related to circular statistics (Berens, 2009 ). For more details, the reader is referred to Mitsis et al ( 2018 ). To investigate whether phase values at seizure onset times were distributed uniformly around the circle from 0 to 2π, we applied the Rayleigh test with the null hypothesis ( H 0 ) being that the population is distributed uniformly around the circle.…”
Section: Eeg Recordings and Preprocessingmentioning
confidence: 99%
“…Using a unique dataset of long-term (days) continuous scalp EEG recordings in patients with epilepsy, we recently showed that the summative properties (degree, efficiency, clustering coefficient) and topology of the resulting functional brain networks exhibit robust long-term periodicities in addition to the well-known circadian 24 h period (Anastasiadou et al, 2016 ; Mitsis et al, 2018 ). Our results demonstrated that brain network periodicities (particularly around 3 and 5 h) are strongly correlated to seizure onset.…”
Section: Introductionmentioning
confidence: 99%
“…We found that functional networks were stronger during sleep than wakefulness, and that they were less clustered when the subject was awake (Burroughs et al, 2014;Kuhnert et al, 2010;Mitsis et al, 2017). The networks were significantly stronger during sleep when compared to wakefulness in all but one subject ( Figure 1B), however, we note that the effects of thresholding networks, even with a proportional threshold, is an active area of research and will require further investigation (Chapeton et al, 2017;Garrison et al, 2015).…”
Section: Discussionmentioning
confidence: 81%
“…In addition to imparting knowledge of how physiological functional networks modulate throughout the day and within waking and sleep states, this will facilitate understanding of changes in network topology due to pediatric diseases such as epilepsy and autism (Righi et al, 2014;Shrey et al, 2018). Seizure forecasting in epilepsy has largely relied on prediction of seizure onset with several minutes of data, but it has been shown that modulations in functional networks due to physiological processes such as waking and sleeping can mask "pre-seizure" changes (Kuhnert et al, 2010;Mitsis et al, 2017;Schelter et al, 2011). Accounting for these physiological fluctuations in seizure prediction models may improve their accuracy and ultimately improve care for patients suffering from epilepsy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation